Modification of the Genetic Polymorphism of Glutathione-S-Transferase (GSTM1 and GSTT1) in Motorcycle Drivers Exposed to BTEX in Cotonou - CACHON, Fresnel Boris; Sagbo, Firmin; Nanoukon, chimène; DJEDATIN, Gustave; ATINDEHOU, Ménonvè; SENOU, MAXIMIN; AYI FANOU, Lucie (My University, 2022)
The glutathione-S-transferase genes mainly the GSTM1 and GSTT1 alleles are responsible for the synthesis of detoxication enzymes that can remove toxic substances. The objective of this study is to seek changes in the genetic polymorphism of glutathione-S-transferase GSTM1 and GSTT1 in motor-cycle drivers exposed to BTEX. Our study group consists of 60 motorcycle drivers including 30 professional and 30 non-professional. Blood samples were preleveled from the study population in the EDTA tubes and DNA was extracted by the phenol/chloroform method. The PCR technique was used to determine the presence or absence of genes. Our results showed that the per-centage of GSTM1 null genotype has a statistically significant difference (P = 0.02), while the percentage of GSTT1 null genotype was non-significant (P = 0.76) between the two groups. The percentage of deletion of both genes is higher in professional than non-professional motorcycle drivers. Air pollu-tion in Cotonou by BTEX seems to influence the deletion of the GSTM1 and GSTT1 genes at a higher percentage among professional than non-professional motorcycle drivers.
Keywords: BTEX; Glutathione-S-Transferase; Deletion; PCR; Motorcycle Drivers